BBC Allegedly Used Leave Campaigners Ideology to Frame EU Referendum - David Randy; Denik Iswardani Witarti (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2021)
The news broadcasted on the BBC Great Debate places issues related to the referendum into two categories: our party (United Kingdom) and their party (European Union). According to Edelman’s news frame theory, BBC, through the BBC Great Debate program, creates specific perspectives by using particular words that influence the way audiences understand reality. This study explores the impact of the BBC ideology on frames of the EU referendum broadcasted on the BBC Great Debate and the changes in the Brits’ political attitudes. This research’s paradigm is constructivism with a qualitative approach, and the analytical method used is Edelman’s news frame analysis model. Based on the findings, despite numerous criticisms expressed by leading UK academics regarding BBC’s alignments with Leave campaigners in the first three months of the campaign, BBC continued to frame biased stories. The news packages broadcasted by the BBC were potentially designed to influence the Brits’ political decision, turning their vote from remain to leave the EU. However, a specific survey on the voters should be conducted to profoundly examine whether the BBC Great Debate had significantly changed their political decisions.